Guided tissue regeneration with bioabsorbable barriers: intrabony defects and class II furcations - Eickholz, Peter; Kim, Ti-Sun; Steinbrenner, Harald; Dörfer, Christof; Holle, Rolf (Journal of periodontology, 2000)
The aim of this study was to compare the effects of guided tissue regeneration (GTR) using 2 different bioabsorbable barriers (control: polylactide acetyltributyl citrate; test: polydioxanon). The polydioxanon barrier is an experimental membrane for GTR therapy that consists of a continuous occlusive barrier that has a layer of slings on the side that is meant to face the mucoperiosteal flap.
Gesehen am 12.03.2021